Determine the Functional Limitations in Activities of Daily Living Through Short Physical Performance Battery Test Among Asthmatic Adults - Hafiza Ayesha Babar, Nadia Anwer, Hanan Azfar, Saman Tauseef, Sara Shahid, Arslan Saleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: To determine the functional restrictions in functional activities of daily lives in middle aged asthmatic adults and association of BMI with limitations in their daily life activities. Method: An observational cross sectional study was carried out at pulmonology opd of Shalamar hospital. A sample of 36 diagnosed asthmatic adults of middle aged with moderate to severe allergic asthma was taken. A Purposive sampling technique was used to conduct the study. Prediction of functional limitations in everyday activities through Short Physical Performance Battery test was determined. Three series of tests named balance test, gait speed test, repeated chair stand test were conducted which were the part of short physical performance battery test. Each test scored 4 and there was the total of 12 score. Those subjects who had less than 10 score were at risk of limitations in their daily life activities in future. Result: Sample of 30 participants were included for this study from age 35 to 55. Out of which 13 participants were of normal weight with BMI of less than 23.9 and 17 were overweight with the BMI ranges from 24.0 to 30.0. Participants with greater BMI were at the high risk of mortality. The results showed that the 13 subjects were overweight had the high risk of mortality, 13 had the risk of functional limitations in activities of daily living and 4 had the good functional status. There was statistical difference between the BMI and Short Physical Performance Battery test score. (P value= 0.001) Conclusion: This study concluded that middle aged asthmatic adults with moderate allergic asthma had greater risk of functional limitations and high risk of mortality due to the disease effect. This study also showed that the predictive value of functional limitations was more pronounced in females with greater BMI than males. Keywords: Allergic asthma, Activities of daily living, Functional Limitations, Short Physical Performance Battery test,